Transcriptomic analysis of the prothoracic gland from two lepidopteran insects, domesticated silkmoth Bombyx mori and wild silkmoth Antheraea pernyi - Bian, Hai-Xu (Sci Rep, 2019)
The prothoracic gland (PG) is an important endocrine organ of synthesis and secretion of ecdysteroids that play critical roles in insects. Here, we used a comparative transcriptomic approach to characterize some common features of PGs from two lepidopteran species Bombyx mori and Antheraea pernyi. Functional and pathway annotations revealed an overall similarity in gene profile between the two PG transcriptomes. As expected, almost all steroid hormone biosynthesis genes and the prothoracicitropic hormone receptor gene (Torso) were well represented in the two PGs. Impressively, two ecdysone receptor genes, eleven juvenile hormone related genes, more than 10 chemosensory protein genes, and a set of genes involved in circadian clock were also presented in the two PGs. Quantitative real time -PCR (qRT-PCR) validated the expression of 8 juvenile hormone and 12 clock related genes in B. mori PG, and revealed a different expression pattern during development in whole fifth larval instar. This contribution to insect PG transcriptome data will extend our understanding of the function and regulation of this important organ.